Pengendalian Sikap Lateral Pesawat Flying wing Menggunakan Metode LQR - Susanto, Try; Ahdan, Syaiful (Program Studi Teknik Elektro Universitas Khairun, 2020)
Unnamed Aerial Vehicle (UAV) technology of drone is widely used to carry out various mission such as photography, disaster monitoring, and area mapping. However, crash can be caused by environmental disturbances that hinders the completion of the mission. Moreover, an automatic control system is needed to handle this. In this study, the LQR control method is used to control the eleven and pitch angle so that the drone is able to maintain a stable lateral attitude. This control method has a fast and strong response in reaching a point of balance. Based on the test results, it show that the LQR control method applied is able to control the pitch angle and is able to make the drone maintain a lateral attitude, as evidenced by the disturbance at a pitch 20Ã¢Ë†Ëœ the drone is able to maintain a lateral attitude with overshoot of 4.23Ã¢Ë†Ëœ, risetime of 0,7 second, settling time of 1,2 second with a steady state error trend of 0,78